Comparison of Systemic Inflammatory Parameters with Anatomical Pathology Results in Differentiating Benign Prostatic Hyperplasia with and without Inflammation: Cross-Sectional Analytics - Andreas Stefan Layardi; Rosadi Putra (Indonesian Journal of Global Health Research, 2026)
Chronic inflammation plays an important role in pathogenesisbenign prostatic hyperplasia (BPH). Anatomic pathology examination is the standard for detecting prostate inflammation, but it is invasive. Systemic inflammation parameters based on peripheral blood counts have the potential to be non-invasive biomarkers. Comparing inflammatory parameters based on peripheral blood counts NLR, PLR, MLR, SII and SIRI with Anatomical Pathology results in comparing BPH with and without inflammation. This research is an analytical cross-sectional study in BPH patients with and without inflammation based on the results of Anatomical Pathology. A total of 334 patients were included in this study, and the sampling technique used was consecutive sampling. Parametersneutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), monocyte to lymphocyte ratio (MLR), systemic immune-inflammation index (SII), andsystemic inflammatory response index (SIRI) were analyzed and compared between groups. AnalysisReceiver Operating Characteristic (ROC) is used to determine the valuecut-off optimal. The median age of patients was relatively homogeneous. In the BPH group with inflammation, Total leukocyte count, absolute neutrophil count, and absolute monocyte count were higher, while absolute lymphocyte count was lower. All systemic inflammation parameters (NLR, PLR, MLR, SII, and SIRI) were significantly higher in the inflammation group (p < 0.001). SII showed the highest AUC value (0.840), followed by NLR (0.829) and SIRI (0.822). Based on our research, it can be concluded that systemic inflammatory parameters have the potential to be used as non-invasive biomarkers to determine whether a person has BPH with inflammation or not.